Forensic prevention outpatient clinic: a treatment evaluation study. Issue 5 (2nd September 2020) - Nitschke, Joachim; Sünkel, Zara; Mokros, Andreas
ABSTRACT: In forensic psychiatry, secondary prevention implies avoiding offences in individuals who are at high risk but have not committed serious offenses in the past. For this purpose, the forensic prevention outpatient clinic at the Ansbach District Hospital was established to provide risk assessment and treatment. To test the treatment effect of the forensic prevention outpatient clinic in terms of dynamic risk factors and global level of functioning, an observational study with a prospective longitudinal design (up to two years) was conducted, which included treatment ( n = 70) and control ( n = 52) groups. After Holm-Bonferroni correction, the treatment interaction effect (time × group) was significant for one of the three dependent variables (i.e., the Historical Clinical Risk Management-20 [HCR-20] Clinical and Risk as well as the Global Assessment of Functioning's [GAF] subtotals). The dynamic risk operationalized by the R-scale of the HCR-20 decreased at a significantly higher rate across time in the treatment than in the control group. However, this effect was not robust against propensity score matching. The findings highlight the potential of secondary prevention for individuals who are at a high risk of committing serious offenses. Replications in larger samples are needed, ideally in randomized controlled trials.